Our experience in the use of cadaveric internal saphenous vein for chronic hemodialysis. - Pereyra Bonasso, Jorge; Alves, Alberto; Porto, Daniel; Gastambide, Carmelo; Saralegui, Gustavo; Zeballos, Javier (Cirugía del Uruguay, 1987)
Performed in a series of fourteen patients with arte• riovenous fistula by the interposition of a cadaveric saphena homogralt in patients wit.h poor superficial ve• nous areas. This procedure was successlul, obtaining in twelve patients functional arteriovenous istulas that could be used in chronic hemodialysis.